Factors Influencing Adoption of Islamic Banking in Morocco: An Exploratory Study - HAFIANE, Mohammed Amine; ALLOUCH, Faissal (Business Perspective Review, 2021)
Purpose: The objective of this research is to explore the factors influencing the choice of Islamic banking services by Moroccan banking customers. Methods: This study is based on an exploratory qualitative study conducted with a sample of forty active users of the banking services (having a bank account), but non-users of Islamic banking products, aged 25 to 60 in Morocco. Results: This research identified factors influencing the choice of Islamic banking services by the Moroccan banking customers, mainly the compatibility of the ethical and economic benefits provided by the Islamic banks with the needs of the potential adoption, as well as the influence of the two variables, namely the perceived complexity and the risk perceived by the potential adopter of the services and products offered by participatory banks in Morocco. Implications: This study allows managers of participatory (Islamic) banks to understand Moroccan’s views as regards Islamic banking products. The major concern of Islamic banks is to increase the number of accounts and deposits of customers to face the challenge of the liquidity crisis. To this end, Islamic banks need to understand the factors that hinder or motivate the adoption of Islamic banking by consumers in Morocco so as to focus on these factors at the level of commercial communication.